4-Carbonyl-2, 6-dibenzylidenecyclohexanone derivatives as small molecule inhibitors of STAT3 signaling pathway. Issue 23 (1st December 2016) - Ji, Peng; Yuan, Congmin; Ma, Shuhua; Fan, Junchao; Fu, Wei; Qiao, Chunhua
Graphical abstract: Abstract: Inhibition of STAT3 signaling pathway is proposed to be a promising strategy for cancer treatment. In this study, a series of 4-carbonyl-2, 6-dibenzylidenecyclohexanone derivatives were prepared and evaluated as anticancer agents. The most potent compound13r was discovered to exhibit antiproliferative activity against a broad rang of cancer cell lines and relatively low cytotoxicity against normal human cells. Besides, 13r effectively suppressed STAT3 expression as well as phosphorylation, and surface plasmon resonance analysis confirmed the direct interaction of13r with STAT3. Docking simulation showed that13r could inhibit STAT3 by targeting SH2 domain. This study provided evidence for these compounds to be further developed as antitumor agents through inhibition of the STAT3 pathway.